2018
DOI: 10.1021/acs.est.7b05197
|View full text |Cite
|
Sign up to set email alerts
|

Stream Mercury Export in Response to Contemporary Timber Harvesting Methods (Pacific Coastal Mountains, Oregon, USA)

Abstract: Land-use activities can alter hydrological and biogeochemical processes that can affect the fate, transformation, and transport of mercury (Hg). Previous studies in boreal forests have shown that forestry operations can have profound but variable effects on Hg export and methylmercury (MeHg) formation. The Pacific Northwest is an important timber producing region that receives large atmospheric Hg loads, but the impact of forest harvesting on Hg mobilization has not been directly studied and was the focus of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…The patterns in Hg T were similar to patterns in TSS leading to moderate to strong positive correlations between these two variables for the whole creek and within each creek reach. Numerous investigators have reported similar positive correlations between Hg concentration and TSS (Brigham et al, 2009; Eckley et al, 2018; Hurley et al, 1998; Whyte & Kirchner, 2000).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The patterns in Hg T were similar to patterns in TSS leading to moderate to strong positive correlations between these two variables for the whole creek and within each creek reach. Numerous investigators have reported similar positive correlations between Hg concentration and TSS (Brigham et al, 2009; Eckley et al, 2018; Hurley et al, 1998; Whyte & Kirchner, 2000).…”
Section: Discussionmentioning
confidence: 70%
“…between Hg concentration and TSS (Brigham et al, 2009;Eckley et al, 2018;Hurley et al, 1998;Whyte & Kirchner, 2000). S6).…”
Section: Numerous Investigators Have Reported Similar Positive Correlationsmentioning
confidence: 99%
“…However, the THg yields observed from these unharvested hillslopes (6–26 ng m −2 day −1 ) were often 2–3x higher than observed in stream waters at catchment scales (0.8–10 ng m −2 day −1 ; Bishop et al., 2009; de Wit et al., 2014; Eckley et al., 2018; Eklöf et al., 2014; Porvari et al., 2003). Similar to the unharvested yields on these hillslopes, the post‐harvest THg yields (12.1–23.5 ng m −2 day −1 ) were consistently higher than those reported in the broader catchment literature (1.3–14.5 ng m −2 day −1 ; Bishop et al., 2009; de Wit et al., 2014; Eckley et al., 2018; Eklöf et al., 2014; Porvari et al., 2003). Post‐harvest, the highest catchment THg yields from the literature were from organic‐soil dominated boreal forests in Europe (de Wit et al., 2014; Eklöf et al., 2014; Porvari et al., 2003), while the lowest were from the more mineral‐soil dominated and steep forests of the western USA (Eckley et al., 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Eckley et al. (2018) observed changes in both the intercepts and overall slopes of DOC‐filtered/particulate Hg relationships in western USA harvested catchments, while Skyllberg et al. (2009) observed an increase in Hg‐DOC ratio in streamwater draining clearcut Swedish boreal forests within 0–4 yr. Conversely, de Wit et al.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation can alter catchment water flow and limit soil erosion. For example, logging operations and wildfires that deplete vegetation can increase catchment soil erosion and the transport of metals to streams and lakes by orders of magnitude (Garcia and Carignan, 1999;Ice et al, 2004;Nappi et al, 2004), and this impact is amplified in catchments that have a steep topography compared to flatter catchments (Davis et al, 2006;Eckley et al, 2018). The parent material (surficial and bedrock geology) is important because it defines the baseline metal concentration and distribution in soils (Utermann et al, 2019;Wuana and Okieimen, 2011).…”
Section: Catchment Contributionmentioning
confidence: 99%